Epitranscriptomics: regulation of mRNA metabolism through modifications. (December 2017) - Peer, Eyal; Rechavi, Gideon; Dominissini, Dan
Highlights: Over 100 types of chemical modifications exist in cellular RNAs. Technological and conceptual breakthroughs identified internal modifications in mRNA. Newly discovered machineries install, remove and bind different modifications. Known as the epitranscriptome, mRNA modifications are essential to gene expression. Modifications affect various cellular, developmental and disease processes The language of mRNA thus seems to be much more elaborate than previously thought. Abstract : Cellular RNAs can be modified post-transcriptionally with dynamic and reversible chemical modifications. These modifications can alter the structure and metabolism of mRNA, but only recent methodological and conceptual advances allowed systematic mapping and functional analysis to unfold the role they play in mRNA biology. Mapping the most common internal mRNA modification, N 6 -methyladenosine (m 6 A), paved the way for the deciphering of other types of mRNA modifications, such as N 1 -methyladenosine (m 1 A). RNA methylation provides dynamic regulation to the processing, export, translation and stability of mRNA molecules, thereby influencing fundamental biological and pathological processes such as differentiation, cellular response to stress and tumorigenesis. This review summarizes the key methods and the recent discoveries in the field of epitranscriptomics through the prism of post-transcriptional mRNA methylation in eukaryotes.